Magnetocrystalline anisotropy energy of a transition metal monolayer: a non-perturbative theory - Moos, Thorsten; Hübner, Wolfgang; Bennemann, Karl-Heinz (Solid state communications, 1996)
The magnetocrystalline anisotropy energy Eanis for a monolayer of Fe and Ni is determined using a fully convergent tight-binding calculation including s-d hybridization. The spin-orbit interaction λso is treated non-perturbatively. Remarkably, we find Eanis ∝ λso2 and important contributions to Eanis due to the lifting of degeneracies near the Fermilevel. This is supported by the calculated decrease of the anisotropy energy with increasing temperature on a scale of several hundred K. Our results clarify the present debate on the origin of Eanis.